THE IMPACT ASSESSMENT OF CRUDE OIL PRICE VOLATILITY ON THE LABOR MARKET: A CASE STUDY OF GABON FOR THE PERIOD (1990-2022) - Salhi, Esam Hadi Al-; Ahmed, Salam Anwar; Mohammed, Hareth Adnan (The journal of contemporary issues in business and government, 2024)
This research explores the dynamic relationship between crude oil price fluctuations and their impact on the labor market, particularly unemployment rates in Gabon during the period 1990-2022. As a country heavily reliant on oil exports, Gabon faces economic vulnerabilities due to uncertainties inherent in global oil markets. The study employs a comprehensive approach encompassing theoretical frameworks, methodologies, and empirical analyses to understand the intricate links between crude oil prices, foreign direct investment, economic growth, and unemployment. The study utilizes the Autoregressive Distributed Lag (ARDL) approach to explore short- and long-run dynamics of the variables under consideration. The empirical results shed light on a long-term positive relationship between crude oil prices and unemployment attributed to the Dutch Disease phenomenon. It is acknowledged that the impact of foreign direct investment on unemployment is multifaceted, influenced by sectoral focus, technological adoption, and economic diversification. Economic growth initially correlates with a decrease in unemployment rates in the short run but exhibits asymmetric effects over time. Diagnostic tests confirm the model's reliability with insignificant serial correlation and residue homoscedasticity. Stability tests validate the consistency of data relationships, confirming the enduring relationships between variables